Waste identification diagrams - Dinis-Carvalho, José (2015)
Value Stream Mapping (VSM) is a very popular tool in lean environments to represent production flows, mapping value stream of a product or family of products, and helps to identify some types of waste. Although very popular, this tool has some limitations as already described in many publications, especially in terms of restrictions in showing most types of waste as well as in its inability to represent various production routes. The purpose of this study is to introduce the waste identification diagram (WID), a new tool to represent production units with its different forms of waste, which overcomes some VSM limitations. The originality of WID comes from the use of its symbols' dimensions to convey, in a visual and immediate way, relevant information about a production unit. In this paper, WID is applied on a production unit of a lift manufacturer, for testing its performance and comparing it to VSM. The main findings are that WID is in general more effective than VSM in terms of representation of complex production units and in terms of identification of more forms of waste. WID must however overcome some of its limitations such as the lack of information-flow representation and the links to suppliers and clients.